Long‐term outcomes of elderly patients receiving continuous flow left ventricular support. Issue 12 (1st October 2020) - Brozzi, Nicolas A.; Cifuentes, Renzo O.; Saba, Isabela C.; Macon, Conrad; Ghodsizad, Ali; Andreopoulos, Fotios; Loebe, Matthias
Abstract: Background: Heart failure is an epidemic affecting over 6 million people in the United States. Eighty percent of all heart failure patients are older than 65 years of age. Heart transplant is the gold standard treatment for patients suffering advanced heart failure, but only 18.5% of patients receiving heart transplant in the United States are 65 years of age or older. Continuous‐flow left ventricular assist devices are a safe and effective therapy for patients with advanced heart failure, and can be used to bridge patients to a heart transplant or to support patients long‐term as destination therapy. Material and Methods: We sought to characterize long‐term outcomes of elderly patients receiving continuous‐flow left ventricular support in our program. Conclusion: Elderly patients with advanced heart failure presented comparable operative results to those of younger patients. The rate of complications up to 6 years of support was low, and comparable to those of younger patients. An effective and safe alternative for patients whom are less likely to receive heart transplantation.